2014
DOI: 10.1158/0008-5472.can-14-0186
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of Chemotherapeutic Response in Ovarian Cancers Using Publicly Available High-Throughput Data

Abstract: A third of patients with epithelial ovarian cancer (OVCA) will not respond to standard treatment.

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
22
0
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 35 publications
(26 citation statements)
references
References 52 publications
3
22
0
1
Order By: Relevance
“…First, we identified a common deletion in H23, OVCAR3 and A2780 cells, induced by cisplatin treatment in chromosome 18, including two completely deleted genes, LRP1B and ITF2. A similar deletion was identified in a previous study analysing cisplatin response in ovarian cancer samples, which supports our results [16]. However, there is another study analyzing the cytogenetic alterations of CDDP-resistant A2780R cells, which shows different genomic alterations.…”
Section: Discussionsupporting
confidence: 92%
“…First, we identified a common deletion in H23, OVCAR3 and A2780 cells, induced by cisplatin treatment in chromosome 18, including two completely deleted genes, LRP1B and ITF2. A similar deletion was identified in a previous study analysing cisplatin response in ovarian cancer samples, which supports our results [16]. However, there is another study analyzing the cytogenetic alterations of CDDP-resistant A2780R cells, which shows different genomic alterations.…”
Section: Discussionsupporting
confidence: 92%
“…In addition to tumour infiltrating lymphocytes (TILs), effector molecules secreted by both tumour and immune cells mediate tumour progression, metastasis and/or response to therapy . Indeed, four molecular subtypes of HGSC were recently defined with the C1 and C2 molecular subtypes of HGSC showing a predominance of immune‐related gene signatures . Interestingly, the C2 subtype shows characteristic higher levels of CXCL9 , CXCL10 and CXCL11 expression as well as higher intra‐epithelial CD3 + T cell infiltration compared to C1 which has a distinct high stromal immune signature .…”
Section: Introductionmentioning
confidence: 99%
“…Another study reported a prognostic and response predictive 97‐gene signature using 7 transcriptomic data sets including the TCGA RNA‐Seq data (total n = 1020 patients) . Salinas et al, 2016 aimed at genetic predisposition to chemotherapy resistance and evaluated 22 007 unique SNPs in the TCGA data set, within a previously reported 422‐gene signature. A total of 19 SNPs were identified as a result of this evaluation; however, these failed validation in independent data sets.…”
Section: Omics In Action: Predicting Chemotherapy Resistancementioning
confidence: 99%